Reopening of School Kiosks Post Pandemic. Proposals from a Look at Healthy Food Environments; [Reapertura de Los Kioscos Escolares Post Pandemia. Propuestas Desde Una Mirada de Entornos Alimentarios Saludables] - Saez-Tonacca, L; Palacios-Pino, J; Pizarro-Quevedo, T; Gonzalez-Araya, D (Sociedad Chilena de Nutricion Bromatologia y Toxilogica, 2023)
[No abstract available]